Planning Study of Solar Power Plant (PLTS) in Lelewi Village, Gane Tengah District, South Halmahera Regency - M. Yunus H Abbas; Iis Hamsir Ayub wahab (Universitas Khairun, 2024)
Lelewi Village, Gane Tengah District, South Halmahera Regency, there are 80 families (heads of families) whose livelihood is farmers and fishermen. Geographically, Lelewi village is located in an area with a fairly high potential for solar energy, making Lelewi village a suitable place for the construction of a Solar Power Plant. Frequent sudden power outages due to lack of load capacity and natural disturbances (such as broken branches and trees and animals) cause a large number of electronic equipment to be damaged. And the operating time of PLN starts from 18.00 â€“ 07.00, so a Solar Power Plant (PLTS) system is designed for use during the day only.So that this research will be discussed in more depth about the Analysis of Power Calculation at Solar Power Plants in Lelewi Village, South Halmahera Regency. To design an electric energy plant so that it meets the load needs for 10 years in Lelewi Village, South Halmahera Regency, it is necessary to carry out a load forecast (forecast electricity load). The method used to carry out load forecasting is the Linear Regretion method. Solar power energy is calculated at 50% of the daily load during the day, total electrical energy that can be generated from solar power plants is 12 Wh.Â The solar components used after accounting for the need for electrical power backup are 48 100 wp solar panels, 48 units of 12V voltage batteries with a capacity of 100 Ah which are expected to be charged in about 10.05 hours, 2 units of solar charger controllers, and 1 unit of inverter with a capacity of 226.25 Watts